INFORMATION TECHNOLOGY PLAN AS AN IT GOVERNANCE MATURITY DRIVER - Budi Yuwono; Rein Nusa Triputra; Muhammad Nasri (Jurnal Sistem Informasi, 2009)
Having an information technology (IT) plan is a minimum baseline for optimal IT governance. But, creating a plan is only one problem, executing it poses even more challenging problems. In this research, we investigate the correlation between an organization’s IT plan and the organization’s IT governance maturity level. We show that, on one hand, executing an IT plan requires a certain IT governance maturity level, on the other hand, the experience of executing an IT plan drives the organization IT governance maturity level. We compare the situations in two government institutions and found indications that the organization with an ambitious IT plan has more mature IT governance than the other whose IT plan is relatively modest. The results suggest that an effective IT plan should include plans for the development of IT governance mechanisms relevant to the goals that the plan is intended to achieve, and the plan’s implementation schedule, also known as the IT roadmap, should take into consideration the growth of the IT governance mechanisms’ maturity levels. Memiliki rencana untuk teknologi informasi (TI) adalah base line untuk tata kelola TI yang optimal. Tapi, membuat rencana hanyalah satu masalah, melaksanakannya akan menciptakan masalah baru yang lebih menantang. Dalam penelitian ini, kami menyelidiki korelasi antara rencana TI suatu organisasi dengan tingkat maturity tata kelola TI-nya. Kami menunjukkan bahwa, di satu sisi, untuk melaksanakan rencana TI memerlukan tingkat kematangan tata kelola TI tertentu, di sisi lain, pengalaman dalam menjalankan rencana TI mendorong organisasi dalam meningkatkan tata kelola TI. Kami membandingkan situasi di dua lembaga pemerintah dan menemukan indikasi bahwa organisasi dengan rencana TI yang ambisius memiliki tata kelola TI lebih matang dari organisasi yang rencana TI-nya relatif sederhana. Hasil penelitian menunjukkan bahwa perencanaan TI yang efektif harus mencakup rencana untuk pengembangan mekanisme tata kelola TI yang relevan dengan tujuan yang ingin dicapai, dan jadwal pelaksanaan rencana atau roadmap TI, harus mempertimbangkan pertumbuhan tingkat mekanisme tata kelola TI.